Transition towards a bioeconomy: Discourses, vantage points, and actors' contextualized institutional work - Kerstin Maria Wilde (Universitäts- und Landesbibliothek Sachsen-Anhalt, 2025)
This thesis explores the status and prospects of transition towards a bioeconomy. It asks how bioeconomy actors' sociotechnical imaginaries, their perception of context conditions and their institutional work contribute to the current status of an emerging bioeconomy. Theoretical concepts from evolutionary economics (innovation systems; sociotechnical systems) and organisational sociology (neo-institutional theory) guided the empirical research. Main results show that transition is held back by insufficient societal deliberations and blurred objectives of bioeconomy promotion. The institutional conditions differ markedly in different industries: the impact on actors' institutional work can be conducive, barricading or exhausting. Progress towards transition appears more likely where institutional logic change is combined with tightening regulation. Policy may strengthen field-level coordination mechanism and help SMEs advancing new quality management systems for a bioeconomy.
urn:nbn:de:gbv:3:4-1981185920-1207984
Keywords: 330